Chemistry - Alesia Sigang Gugkang; Thitiporn Na Nakorn; Geoffrey Harvey Tanakinjal; Asfarina Abu Bakar; Nurzafirah Mazlan; Jazirotur Rohmah; Christophe Wiart (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2024)
The luxury supplychains are called to realign their focus from a sustainability point of view. Affluent consumers are called for product visibility to ensure transparency is mainly on social inclusion. However, on-going debates are known in sustainability initiatives due to the complexity and uncertainty of standard guidelines and what counts as a successful or excellent implementation. Since luxury is a much visible industry that attracts public attraction on their association with the increase of social inequality between the richest and the poorest in the country - hence, this paper offers both a conceptual review and a research agenda – towards advancing this field of study and bridging the gap between existing research and future research. In conclusion, we propose three areas of future research on: (i) enablers and challenges, (ii) the role of stakeholders and (iii) how luxury organisations cope with institutional complexities of implementing social sustainability.